Video feedback control of pulverized coal flow - Arellano Sanzol, Juan (2001)
This master’s thesis deals with the single-line control of pulverized coal flow into a blast furnace. Towards this end a coal flow estimate based upon video image analysis is used as a soft sensor. The pulverized coal injection has been studied through identification experiments and subsequent data analysis. Mathematical black-box models for the dynamics between the flow control valve and the soft sensor output have been developed. A control structure has been suggested, and the first steps towards controller implementation have been completed. The objective is to minimize the variations of the coal flow into the blast furnace. Problems associated with the implementation of the scheme discussed and recommendations are done for further work on used video image analysis for control purposes. All experiments have been performed at blast furnace no.3 (lance 4) at SSAB Tunnplåt AB Luleå, Sweden. Validerat; 20101217 (root)